Human Embryo Metaphysics and the New Biotechnologies - Sullivan, Dennis M. (Christian scholar's review, 2016)
Much of Christian scholarship has defended the Conception View of personhood, the idea that human beings have intrinsic value that begins at conception. However, modern reproductive technologies have led to new scientific insights into human embryology, without a matching increase in our metaphysical and moral understandings. A rigorous formulation of human nature and personhood is therefore needed. This paper explores and defends an ancient yet still prominent framework for human identity called hylomorphism, updated to match our current biological understandings and biotechnological innovations. In particular, we apply this framework to the ethical analysis of several kinds of new research, including a controversial intervention that treats mitochondrial diseases. We conclude with reasons why this understanding is crucial to the most prominent Christian understanding of human dignity.